Clinical features and induction outcome of childhood acute lymphoblastic leukemia in a lower/middle income population: A multi‐institutional report from Pakistan. Issue 10 (15th May 2015) - Fadoo, Zehra; Nisar, Imran; Yousuf, Fatimah; Lakhani, Laila Saleem; Ashraf, Shamvil; Imam, Uzma; Zaheer, Junaid; Naqvi, Ahmed; Belgaumi, Asim
<x xml:space="preserve">Abstract</x> Background Acute lymphoblastic leukemia (ALL) is the most common cancer of childhood. Some evidence suggests differences in clinical and cytogenetic characteristics of ALL based on geographic and ethnic variations. However, data on ALL characteristics and early outcome of therapy from low/middle‐income countries such as Pakistan are scanty. Procedure A prospective, multi‐institutional cohort study in Karachi enrolled 646 newly diagnosed children with ALL over 3 years. Standard forms were used to collect demographic, clinical, and laboratory data at presentation and at the end of induction. Results Of the total, 66.1% (n = 427) were males. Median age was 6 (mean ± SE 6.87 ± 0.16; range 0.16–18) years. The most common clinical presentation was fever (88.7%). BPC‐ALL was diagnosed in 78.5%, while 17.5% had T‐ALL; 28.8% had a WBC >50 × 109/L. With 316 patients karyotyped, hypodiploidy and hyperdiploidy were seen in 5.1% and 10.7%, respectively. Of those tested, ETV6‐RUNX1 translocation was detected in 13.2%, while BCR‐ABL1 translocation and MLL gene rearrangements were seen in 7.3% and 4.6%, respectively. The cumulative loss to follow up before and during induction was 12.8% (n = 83) and 11.5% (n = 74) died before or during this phase. Induction was successfully completed by only 75.6% (n = 489) of the entire cohort and 69.6% (n = 450) achieved remission. Conclusion These patients had ALL with higher risk features than that reported from developed countries. One quarter failed to complete induction chemotherapy. This suboptimal result requires further study and development of innovative interventions, particularly focusing on the causes and solutions for late referral, abandonment, and infections. Pediatr Blood Cancer 2015;62:1700–1708. © 2015 Wiley Periodicals, Inc.